Inter-Relationship of Potassium with other Soil Fertility Parameter in Two Major Wetland Rice Soils of Kerala - Naveen Leno (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1997)
A study was done at the College of Agriculture, Vellayani during 1994-95 to quantify the different forms of potassium and to investigate the inter-relationships of these forms with other soil fertility parameters. Soil samples were collected from ten locations each, of the two major wet land rice soils of Kerala selected for the study viz., lateritic alluvium of Pattambi (brown hydromorphic) and Onattukara sandy soil (greyish Onattukara) of Kayamkulam. Incubation studies were also carried in both soil types, with and without applied potash, for a period of two months. The study revealed that considerable variation existed in the physico-chemical properties of the two soils. The lateritic alluvium of Pattambi was clayey, high in chloride, organic matter, active iron, CEC, ECEC, exchangeable Ca, Mg and sum of bases and was low with respect to coarse sand and available phosphorus contents and was less acidic as compared to the Onattukara sandy soils of Kayamkulam. The latter was loamy sand in texture with a high content of coarse sand fraction, more acidic, high in phosphorus content and low in clay, chloride, organic matter, active iron, CEC, ECEC, exchangeable Ca, Mg and sum of bases in comparison to the former.